2014
DOI: 10.3899/jrheum.130346
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Diastolic Dysfunction in Patients with Dermatomyositis Without Clinically Evident Cardiovascular Disease

Abstract: Our study confirms a high frequency of LVDD in DM patients without evident CV disease. The association between transmitral flow alteration and disease duration may suggest a subclinical myocardial involvement with disease progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 34 publications
4
18
0
Order By: Relevance
“…There are only a few controlled studies on PM/DM using newer echocardiographic techniques like TDI. In accordance with our study, 2 recent studies on Asian populations using TDI reported a significantly higher frequency of LVDD in patients with PM/DM compared to HCs (12,13). Similar findings have been reported in a followup study of patients with juvenile DM (43).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…There are only a few controlled studies on PM/DM using newer echocardiographic techniques like TDI. In accordance with our study, 2 recent studies on Asian populations using TDI reported a significantly higher frequency of LVDD in patients with PM/DM compared to HCs (12,13). Similar findings have been reported in a followup study of patients with juvenile DM (43).…”
Section: Discussionsupporting
confidence: 82%
“…Importantly, LVDD can develop into heart failure and is an independent predictor of mortality in the general population (11). However, few controlled studies in patients with PM/DM have used TDI to measure LVDD (12,13); one of these studies showed significantly increased frequency of LVDD in DM patients (76.5%) versus controls (52.9%) (13). Tc-pyrophosphate ( 99m Tc-PYP) scintigraphy can be useful to detect inflammation in skeletal and cardiac muscles in patients with PM/DM (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Lu and coworkers found in patients with PM/DM that female sex, late onset, and long disease course were 3 independent risk factors in the development of LV diastolic dysfunction 9 . Moreover, Wang, et al demonstrated a significant relationship between the changes in the diastolic variables and the disease duration in patients with DM, similar to what has been shown in rheumatoid arthritis (RA) and systemic sclerosis 11 .…”
Section: Journal Of Rheumatologymentioning
confidence: 73%
“…These results mainly included early LV diastolic dysfunction 9,10,11 , which may serve as a precursor for systolic and diastolic heart failure. Lu and coworkers found in patients with PM/DM that female sex, late onset, and long disease course were 3 independent risk factors in the development of LV diastolic dysfunction 9 .…”
Section: Journal Of Rheumatologymentioning
confidence: 98%
See 1 more Smart Citation